Understanding the gut microbiome through a fitness intervention of aerobic and resistance training for individuals with type 2 diabetes mellitus (GUTFIT: A Study Protocol) - Amy M. Thomson; Dominique C. Drost; Neil M. Johannsen; Cristoforo Silvestri; Martin Sénéchal (PLoS ONE, 2026)
Introduction Exercise is a cornerstone of type 2 diabetes (T2DM) management, yet individuals exhibit vast inter-individual variability in glycemic response to interventions. Gut microbial diversity and exercise intensity may be factors influencing this response variability. However, the interplay between exercise intensity, microbial adaptations, and glycemic outcomes in individuals living with T2DM remains unclear. Objectives The purpose of this protocol is to describe the GUTFIT study, which aims to test whether performing vigorous-intensity combined aerobic and resistance training produces greater changes in glycemia and gut microbial diversity than moderate-intensity training in individuals living with T2DM. A secondary objective is to explore whether decreases in glycemia after exercise are associated with alterations in gut microbial community architecture and diversity. Methods The GUTFIT Study (NCT06268743) is a parallel-group, single-blinded, randomized trial involving 40 adult participants (n = 20 female) living with T2DM. Participants will be randomized to 16 weeks of: 1) vigorous-intensity exercise (aerobic training at 70–80% heart rate reserve and resistance training at 8–10 repetitions of 75–80% maximal strength) or 2) moderate-intensity exercise (aerobic training at 45–55% heart rate reserve and resistance training at 12–15 repetitions of 65–70% maximal strength). Glycemia will be measured via glycated hemoglobin (HbA1c), and gut microbial composition will be determined in participant fecal samples using next-generation sequencing (Illumina MiSeq) of 16S ribosomal DNA genes. All outcome measures will be tested pre- and post-intervention. Discussion Results of this study will provide further insight into the role of exercise intensity in changes in glycemia and the gut microbiome, and whether there is an intensity-dependent association between exercise-induced changes in glycemia and gut microbial diversity in individuals living with T2DM.